Implementation of Hybrid Cloud Architecture: A Data Scalability Solution in The Msme Sector - Muhammad Singgih Zulfikar Ansori; Arif Surachman; Miftakhus Surur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Micro, Small, and Medium Enterprises (MSMEs) face significant challenges in managing data volatility and digital transformation costs. This research explores the implementation of hybrid cloud architecture as a strategic solution for data scalability within the MSME sector. Using a qualitative descriptive approach supported by a systematic literature review, this study analyzes how hybrid cloud integration balances the cost-efficiency of public clouds with the security and control of private infrastructures. The findings indicate that hybrid cloud systems allow MSMEs to scale their operational data dynamically during peak periods without incurring prohibitive capital expenditures. Furthermore, the study identifies that technical readiness and managerial support are critical determinants in successful cloud adoption. This research provides a framework for MSME owners and policymakers to enhance digital competitiveness through scalable IT infrastructure.